Stravaganza, city of stars - Hoffman, Mary (Bloomsbury, 2005)
Fifteen-year-old Georgia, who loves horses as much as she hates her bullying stepbrother, buys a figurine of a winged horse and finds it has magical powers that transport her from present-day London to the sixteenth-century world of Talia.